Powtoon Based Physics Learning Video Development on Straight Movement Materials for Class X SMA - Ali Chandra; Muhammad Nasir; Fakhruddin Z (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2021)
The aim of this research was to produce a valid Powtoon-based physics learning video on straight motion material for class X senior high school. The product developed is in the form of a physics learning video based on Powtoon on straight motion material for class x senior high school. The research method uses the ADDIE development model with five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instrument used is a validation sheet that is given to experts in providing an assessment of the validity of the media. The assessment instrument includes four aspects of the assessment, namely the design aspect, the pedagogic aspect, the content aspect, and the technical aspect. The results of the validation of these four aspects obtained an average score of 4.34. Video meeting 1 got the final score with a value of 4.31. Video meeting 2 got the final score with a value of 4.36. Video meeting 3 got the final score with a value of 4.37. Powtoon-based physics learning media has been successfully designed for three meetings which include straight motion learning material in class X SMA. This learning media has been successfully created using the powtoon application. This learning media has been validated by experts. All experts have stated that every element of the assessment of this learning media is valid, so it is suitable to be used as a medium for learning physics in straight motion material.